Electrospinning vs. Electro-Assisted Solution Blow Spinning for Fabrication of Fibrous Scaffolds for Tissue Engineering; Polymers; Vol. 14, iss. 23 - Demina T. S. Tatyana Sergeevna; Bolbasov E. N. Evgeny Nikolaevich; Peshkova M. A. Maria Aleksandrovna; Efremov Yu. M. Yuri Mikhailovich; Bikmulina P. Yu. Polina Yurievna; Birdibekova A. V. Aisylu Vakhitovna; Popyrina T. N. Tatyana Nikolaevna; Kosheleva N. V. Nastasia Vladimirovna; Tverdokhlebov S. I. Sergei Ivanovich; Timashev P. S. Peter; Akopova T. A. Tatyana (2023, 2023)
Biodegradable polymeric fibrous non-woven materials are widely used type of scaffolds for tissue engineering. Their morphology and properties could be controlled by composition and fabrication technology. This work is aimed at development of fibrous scaffolds from a multicomponent polymeric system containing biodegradable synthetic (polylactide, polycaprolactone) and natural (gelatin, chitosan) components using different methods of non-woven mats fabrication: electrospinning and electro-assisted solution blow spinning. The effect of the fabrication technique of the fibrous materials onto their morphology and properties, including the ability to support adhesion and growth of cells, was evaluated. The mats fabricated using electrospinning technology consist of randomly oriented monofilament fibers, while application of solution blow spinning gave a rise to chaotically arranged multifilament fibers. Cytocompatibility of all fabricated fibrous mats was confirmed using in vitro analysis of metabolic activity, proliferative capacity and morphology of NIH 3T3 cell line. Live/Dead assay revealed the formation of the highest number of cell–cell contacts in the case of multifilament sample formed by electro-assisted solution blow spinning technology.